Correction: Mass Spectral Similarity Networking and Gas-Phase Fragmentation Reactions in the Structural Analysis of Flavonoid Glycoconjugates (Analytical Chemistry (2019) 91:16 (10413-10423) DOI: 10.1021/acs.analchem.8b05479) - Pilon, Alan Cesar [UNESP]; Gu, Haiwei; Raftery, Daniel; Da Silva Bolzani, Vanderlan [UNESP]; Lopes, Norberto Peporine; Castro-Gamboa, Ian [UNESP]; Carnevale Neto, Fausto [UNESP] (American Chemical Society (ACS), 2019)
Because of a production error, Figure 3 was incorrectly duplicated as Figure 4. Please find here the correct Figure 4. In Table 2, please consider Yi,j + rather than Yi,i+.